The development of the world and classical work on the Kazakh scene - Mayemitov, А. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2016)
This article widely analyzes directorial decisions and acting skillsin context of the continuity and innovation the world and russian classical performances staged in several theaters of our republic.Also analyzes with modern interpretations of scene images, genre of other conversion character, the revival content and forms of the dramatic and musical compositions. Than they give assess for performance and for directing searches and experiments.